Relationship of Self-Confidence, Perception of Barriers, and Partner Support with Providing Reproductive Health and Sexuality Information from Parents to Adolescents - Tanjung Anitasari Indah Kusumaningrum; Diah Laras Suci; Dini Wulandari (International Journal of Public Health Science (IJPHS), 2022)
Adolescence is a period of searching for identity that requires information on reproductive health and sexuality so as not to fall into premarital sexual behavior. Parents play an important role in providing reproductive health information to adolescents, but parents are often reluctant to provide this information due to lack of support, and lack of confidence in providing reproductive health information. The purpose of this study was to determine the most influential factors between partner support, perceived barriers, and self-confidence in adolescent reproductive health education. The research method used analytical observation with a cross sectional approach which was conducted online in June-August 2020 to 300 parents who have teenagers aged 15-19 years in Surakarta. The sampling technique is Double Sampling using a self-confidence, partner support, perceived barriers and behavior in providing reproductive health information questionnaire that has been tested for validity. Bivariate analysis was performed using chi square and multivariate analysis was performed using logistic regression test. The results showed that parents' self-confidence was the most influential factor in reproductive health education for adolescents (OR=3.052, CI=1.534-6.071). Parents who have low self-confidence tend not to provide comprehensive reproductive health information to adolescents. Lack of skills to explain the topic of sexuality to teenagers is one of the things that affects parents' self-confidence. The lack of knowledge of the material that will be given and the shame when conveying sexuality material also affects the self-confidence of the parents. Training efforts are needed for parents on how to provide information on reproductive health to adolescents.